How do i find the general solution of this equation using laplace transform?? its a practice problem for my exam but im not sure how to solve it.
y'''-4y'=0 when y(0)=1, y'(0)=2, y(0)''=-20
The laplace transform of
$\displaystyle \frac{d^ny}{dt^n}=s^nY-\sum_{k=0}^{n-1}s^{n-k-1}y^{k}(0)$
So in your case
$\displaystyle \mathcal{L}\{y'''\}=s^3Y-s^2y(0)-sy'(0)-y''(0)=s^3Y-s^2-2s+20$
and
$\displaystyle \mathcal{L}(y')=sY-1$
This gives the algebraic equation
$\displaystyle s^3Y-s^2-2s+20-4(sY-1)=0$
Now just solve for Y and invert the transform